Thesis: A SPECTROSCOPIC STUDY OF POLYMER ELECTROLYTE MEMBRANES - Yan, Zhejia Blossom (My University, 2018)
This thesis focuses on the state-of-the-art spectroscopic approaches in studying polymer electrolytes for proton exchange membrane fuel cells. With the aim to optimize architectural and chemical design of hydrogen fuel cells, a variety of perfluorosulfonic acid (PFSA) membranes were explored to establish characteristics that ultimately improve PFSA electrolyte performance. The results of the detailed spectroscopic analyses helped to unveil a structure performance relationship. Solid-state nuclear magnetic resonance (ssNMR) spectroscopy was used to distinguish F and C environments, while scanning transmission X-ray microscopy coupled with X-ray absorption spectroscopy provided complementary chemical structural information with direct access to S and O environments. The combination of these two techniques provided advantages in identifying subtle chemical alterations in PFSAs. Furthermore, a novel ssNMR technique was developed with the purpose of probing local dynamics from the polymer perspective. This ¬¬19F dipolar recoupling ssNMR approach was validated and applied to PFSA membranes by monitoring the normalized double quantum build-up curves as a function of relative humidity (%RH) and temperature, and the polymer side chain showed higher local motion as response to temperature and %RH elevation compared to the backbone. The effective dipolar coupling constant was extracted to represent local dynamics and compared amongst tested PFSAs. A standardized metric, the dynamic order parameter, was also introduced and applied to the materials to quantitatively compare them within the same class. This new method provided an alternative way to extract site-specific local dynamics profile for materials with multiple resonances. Additionally, the combination of in situ fuel cell performance evaluation and ex situ ssNMR characterization created a connection between fundamental chemistry and bulk electrochemical measurements. As the first study to correlate these physicochemical properties to material performances, this work parameterized the structural impact at a molecular level and provided insight into improving polymer electrolyte materials.
A SPECTROSCOPIC STUDY OF STRUCTURE AND DYNAMICS IN PROTON-CONDUCTING POLYMERS FOR HYDROGEN FUEL CELLS
Keywords: Solid-State NMR; Electrochemistry; Hydrogen Fuel Cell; PFSA; Polymer Electrolyte; STXM; NEXAFS; Physical Chemistry